Kinetic regularities of neopentyl glycol esterification with acetic and 2-ethylhexanoic acids - D. S. Chicheva; E. L. Krasnykh; V. A. Shakun (Тонкие химические технологии)
Objectives. Development of a domestic technology for producing environmentally friendly non-phthalate plasticizers, lubricants and transformer fluids based on neopentyl glycol (NPG), an oxo-synthesis product.Methods. The methodology of the work was to study the kinetic laws of NPG esterification with acetic and 2-ethylhexanoic acids under self-catalysis conditions with an 8-fold molar excess of monocarboxylic acids. The production of NPG esters was carried out by azeotropic esterification in the presence of solvents—benzene and m-xylene. The resulting diesters were isolated from the reaction mass by vacuum rectification. The purity of the obtained NPG diesters was no less than 99.7 wt %. Analysis of the qualitative and quantitative composition of reaction samples was carried out using infrared spectroscopy, gas chromatography–mass spectrometry and gas–liquid chromatography.Results. The paper presents the results of kinetic studies on NPG esterification of with acetic and 2-ethylhexanoic acids. It compares the reaction rates and reactivity of the acids used. Under the given conditions, NPG diesters were produced, and some of their physicochemical properties were determined. This enabled the data obtained to be used for the development of industrial technology in the production of NPG diesters.Conclusions. It was established that with an eightfold molar excess of acid under self-catalysis conditions, a yield of NPG diacetate equal to 95% is achieved within 20–22 h at an optimal process temperature of 100–110℃; NPG di(2-ethylhexanoate)—within 26–28 h at 160–170℃. The activation energies and pre-exponential factors for the formation of NPG mono- and diesters with acetic and 2-ethylhexanoic acids were established. The paper presents the kinetic models of esterification.